2019
DOI: 10.1038/s41598-019-50890-x
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive factors and risk of external causes of death among women: The Japan Public Health Center-based Prospective Study (JPHC Study)

Abstract: Although empirical data suggest a possible link between female reproductive events and risk of nonfatal accidents and suicidal behaviors, evidence to determine these effects on mortality is scarce. This study investigated the association between female reproductive factors and the risk of external causes of death among middle-aged Japanese women. We used a population-based cohort study consisting of 71 698 women residing in 11 public health center areas across Japan between 1990 and 1994. Multivariable-adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
2
5
0
1
Order By: Relevance
“…14,15 For example, one study from Australia showed that all-cause mortality in women decreased with increasing parity. 11 Similar findings were reported in a Japanese study, 12 in which parous women had an HR of 0.67 (95% CI 0.46–0.97) for all-cause mortality. A fairly recent meta-analysis showed that those with no live birth had a significantly elevated risk of all-cause mortality compared with participants with one or more live births.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…14,15 For example, one study from Australia showed that all-cause mortality in women decreased with increasing parity. 11 Similar findings were reported in a Japanese study, 12 in which parous women had an HR of 0.67 (95% CI 0.46–0.97) for all-cause mortality. A fairly recent meta-analysis showed that those with no live birth had a significantly elevated risk of all-cause mortality compared with participants with one or more live births.…”
Section: Discussionsupporting
confidence: 81%
“…1113 One Australian study 11 clearly shows that all-cause mortality in women decreased with increasing parity. Another study from Japan 12 showed similar findings, i.e. lower all-cause mortality in parous women.…”
Section: Influence Of Life Events On Expression Of Personality Disordersupporting
confidence: 60%
See 3 more Smart Citations